2015
DOI: 10.1111/1745-9125.12075
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Risk Among Victims of Youth Violence: Are Early Unions Bad, Beneficial, or Benign?

Abstract: Youth violent victimization (YVV) is a risk factor for precocious exits from adolescence via early coresidential union formation. It remains unclear, however, whether these early unions 1) are associated with intimate partner violence (IPV) victimization, 2) interrupt victim continuity or victim–offender overlap through protective and prosocial bonds, or 3) are inconsequential. By using data from the National Longitudinal Study of Adolescent to Adult Health (N = 11,928; 18–34 years of age), we examine competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
(115 reference statements)
1
13
0
3
Order By: Relevance
“…We also recognize that our combined measure of IPV may mask important differences between victimization and perpetration experiences. Given that some populations are particularly at risk for IPV [32, 33, 34], future work should strive to untangle these intricacies. Additionally, our measure did not assess severity, frequency, or injury.…”
Section: Discussionmentioning
confidence: 99%
“…We also recognize that our combined measure of IPV may mask important differences between victimization and perpetration experiences. Given that some populations are particularly at risk for IPV [32, 33, 34], future work should strive to untangle these intricacies. Additionally, our measure did not assess severity, frequency, or injury.…”
Section: Discussionmentioning
confidence: 99%
“…The key independent variable, adolescent violent victimization , is a binary variable measured at wave 2 that reflects whether respondents were victims of violence in the past year (1 = yes, 0 = no). Respondents were coded as being violently victimized if they reported that any of the following things had happened over the past 12 months: “someone pulled a knife or gun on you,” “you were jumped,” “someone stabbed you,” and “someone shot you.” This measure has been used consistently in prior research (Fang & Corso, ; Kuhl et al., ; Turanovic & Pratt, ). Approximately 15 percent of the sample experienced violent victimization at wave 2.…”
Section: Methodsmentioning
confidence: 99%
“…Study findings have shown that, in adulthood, those who were victimized as youth tend to complete fewer years of schooling (Haynie, Petts, Maimon, & Piquero, 2009;Wilczak, 2014), are more likely to be involved in crime (Farrell & Zimmerman, 2018), and are at a greater risk of depression and anxiety (Copeland, Wolke, Angold, & Costello, 2013;Stapinski et al, 2014). Adolescent victims also tend to experience violence in interpersonal relationships in adulthood (Exner-Cortens, Eckenrode, & Rothman, 2013;Kuhl, Warner, & Warner, 2015) and suffer from physical health issues (Ackard, Eisenberg, & Neumark-Sztainer, 2007;Boynton-Jarrett, Ryan, Berkman, & Wright, 2008). The long-term negative effects of adolescent victimization, thus, do not seem to be limited to a particular type of life outcome, but instead they represent an array of problems with involvement in crime and deviance, physical and mental health, and educational and socioeconomic attainment (Macmillan, 2001).…”
Section: Consequences Of Adolescent Violent Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context, the aimed target-group are the youth in law conflict at the Executive Penal Resolution Institutions. Studies in the field have revealed that juvenile criminal behavior is produced by the inapproriate parental practices (Kuhl et al, 2015) that constitute one of the causes and predictors most powerful of delinquency. In comparison to the children of families without behavioral issues, in the families with children who show these forms of matters, it is thought that they unintentionally reinforce the negative behavior of children.…”
Section: Introductionmentioning
confidence: 99%